Rethinking Blindness and Femininity Through Feminist Disability in All The Light We Can Not See by Anthony Doerr - Agry Pramita (Ideas Publishing, 2025)
This study examines Anthony Doerr’s All the Light We Cannot See through the lens of feminist disability theory, particularly the works of Rosemarie Garland- Thomson. It aims to explore how blindness and femininity are portrayed not as deficits, but as alternative forms of knowledge, agency, and resistance. The analysis centers on the character of Marie-Laure LeBlanc, a blind young girl whose heightened sensory perception, emotional strength, and quiet resilience defy traditional stereotypes of disability and female passivity. Employing a qualitative research method based on library research and textual analysis, the study investigates how Doerr’s narrative construction of Marie-Laure challenges dominant visual norms, narrative, and patriarchal representations. Key findings highlight blindness as a valid and complex way of knowing, the politics of visibility and invisibility, and the role of social context and support systems in shaping disabled subjectivity. The study concludes that All the Light We Cannot See contributes to a broader literary and cultural recognition of disability and femininity as meaningful, dignified, and agentive states of being.